High Risk Minority Student Retention Model: A Collaborative Program for Black Students - Thomas E. Midgette; Charles Stephens (Educational Considerations, 1990)
The High Risk Minority Student Retention Program (HRMS) was developed to enhance Black student retention at a large urban Ohio university.